Critical Perspectives on Indonesia Village Development Index - Maria Lusiana Florentin Werang; Priscilia Yolandasari; Yeni Husnaeni; Mia Rizki; Nicolaus Petrus Likuwatan Werang (Jurnal Administrasi Publik, 2025)
The IDM provides a critical instrument for evaluating rural development in Indonesia, yet its current conceptualization demonstrates significant methodological limitations. This systematic literature review critically examines the structural deficiencies within the IDM framework, focusing on its inadequacies in comprehensively capturing the multifaceted nature of rural transformations. While the IDM traditionally emphasizes infrastructure, social services, and economic dimensions, the research reveals substantial gaps in addressing essential developmental components serving as participatory governance, regional heterogeneity, and socio-economic complexity. The study systematically deconstructs the existing IDM model through a comprehensive analytical approach, identifying critical omissions, including geographic isolation challenges, nuanced human development indicators, and pervasive financial inequalities. The research methodology employed a rigorous, systematic literature review, synthesizing multiple scholarly perspectives to illuminate the model’s conceptual constraints. Key findings underscore the imperative for a more sophisticated, context-sensitive developmental framework that integrates localized strategies and collaborative methodological approaches. The implications are profound, suggesting that a recalibrated IDM could significantly enhance policymakers’ perception of rural dynamics, ultimately facilitating more effective interventions that authentically reflect communities based on local preferences.